Assessment of infl uence of osteoplastic materials on the regeneration of bone tissue after resection of the root apex of tooth using computed tomography (LLC "Endo Press", 2020)
Currently tooth-saving operations do not lose their relevance in dentistry. To achieve the desired result osteoplastic material are used to speed up the process of regeneration in the area of the bone's defect. There is a wide choice of osteoplastic materials. It is also a huge amount of research on the eff ectiveness of these materials. However, in the literature there are confl icting reports about them. With the help of computer tomography were obtained data on bone density in the area of operation cystectomy with simultaneous radiectomy using demineralized spongiosis «Lioplast»® and material «CrossBone»®.